Linear Mixed-Effect Models Through the Lens of Hardy–Weinberg Disequilibrium - Zhang , Lin; Sun , Lei (Frontiers in Genetics, 2022)
For genetic association studies with related individuals, the linear mixed-effect model is the most commonly used method. In this note we show that, contrary to the popular belief, this standard method can be sensitive to departure from Hardy-Weinberg equilibrium (i.e. Hardy-Weinberg disequilibrium) at the causal SNPs in two ways. First, when the trait SNP-heritability is treated as a nuisance parameter, although the association test has correct type I error control, the resulting heritability estimate can be biased, often upwardly so, in the presence of Hardy-Weinberg disequilibrium. Second, if the true heritability is used in the linear mixed-effect model, then the corresponding association test can be biased in the presence of Hardy-Weinberg disequilibrium. We provide some analytical insights along with supporting results from simulation and application studies.